(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The present study was undertaken to evaluate the organoleptic, specific gravity, chemical and microbiological qualities of morning and evening milk which collected from Bangladesh Agricultural University Dairy Farm, Mymensingh. In this purposes, six Holstein Friesian crossbred cows were selected for this study. Milk samples were collected every morning and evening immediately after milking and then subjected to test all mentioning parameters. Morning milk showed less yellowish than evening milk whereas flavor, body and texture were found normal in both intervals of milk. Specific gravity was found higher (1.030 ±0.000) in morning milk than evening and significantly (p<0.01) higher fat content observed in evening milk sample due to the more exercise the whole day. Again, total solids, solids-not-fat, protein and lactose content of milk showed significant difference at p<0.05. Other parameters like acidity percent and ash did not show any significant difference. Significantly (p<0.05) higher coliform count was noticed in morning milk than evening milk and non-significant (p>0.05) difference found in total viable count of both intervals milk. Considering the research findings, it might be said that evening milk was better than morning milk. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 255-260